2021
DOI: 10.15622/ia.20.6.2
|View full text |Cite
|
Sign up to set email alerts
|

Effective Functioning of a Mixed Heterogeneous Team in a Collaborative Robotic System

Abstract: The study describes a collaborative robot (cobot) as one of the types of intelligent robotics and its distinctive features compared to other types of robots. The paper presents a collaborative robotic system as a single complex system in which actors of different types – cobots and human workers – perform collaborative actions to achieve a common goal. Elements of a collaborative robotic system, as well as processes and entities that directly influence it are represented. The key principles of Human-Robot Coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…Robots in the industrial sector must follow safety regulations and have been proved to save a significant amount of time and money. Collaborative robots were developed for carrying out activities combinedly by human operators and robots in a shared configuration space [21]. A team of mobile manipulators used for carrying payload was presented in [22].…”
Section: Applications Of Mobile and Modular Robotmentioning
confidence: 99%
“…Robots in the industrial sector must follow safety regulations and have been proved to save a significant amount of time and money. Collaborative robots were developed for carrying out activities combinedly by human operators and robots in a shared configuration space [21]. A team of mobile manipulators used for carrying payload was presented in [22].…”
Section: Applications Of Mobile and Modular Robotmentioning
confidence: 99%
“…During the last 10 years, a lot of research has been reported on the studies and implementation of collaborative robots in various industrial sectors [19] [20]. As part of our research, we analyzed more than 100 cases of collaborative interaction of UR family robots with humans as part of the manufacturing process [15].…”
Section: Typical Use Cases For Collaborative Industrial Robots Ur3 An...mentioning
confidence: 99%
“…The results obtained in the article show that the proposed solution can be applied in walking robots, including anthropomorphic ones for the implementation of stable gait algorithms. Besides the using of developed solutions can have significant influence on development of cyber-physical systems and collaborative robotics [30].…”
Section: программные и аппаратные средстваmentioning
confidence: 99%